APPLICATION OF INTERACTIVE LEARNING MEDIA WORDWALL IN PANCASILA EDUCATION LEARNING TO IMPROVE LEARNING OUTCOMES OF GRADE V STUDENTS OF SD NEGERI 1 LUBUKLINGGAU - desianaawaliya putriariska (CV Grasta Glory, 2026)
This study aim to determine whether the interactive learning media word wall can improve the civic education learning outcomes of fifth grade students at SD Negeri 1 Lubuklinggau. This research used classroom action research (CAR) with 22 students as the subjects , data were collected using observation, tests, and documentation, and analyzed quantitatively. the study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. the results showed a significant improvement in learning outcomes, in cycle I, Student mastery increased from 9% to 40%. in Cycle II, mastery improved to 86.37%. these findings indicate that the interactive learning media wordwall is effective in improving civic education outcomes for fifth-grade students